2023
DOI: 10.1021/acs.analchem.3c00792
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Oxidized Glycerophosphoethanolamines via Radical-Directed Dissociation Tandem Mass Spectrometry and the Paternò–Büchi Derivatization

Abstract: Oxidized glycerophosphoethanolamines (oxPEs) represent a subclass of bioactive lipids that have intricate roles in various physiological and pathological events. Conventional mass spectrometric methods cannot provide unambiguous information to locate the OH group and the sites of unsaturation. Herein, we report a combined strategy for in-depth structural characterization of oxPEs, including radical-directed dissociation tandem mass spectrometry (RDD-MS/MS) for localizing the OH group and the Paternò–Büchi de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…3-(2,2,6,6-Tetramethylpiperidin-1-yloxymethyl)-picolinic acid 2,5-dioxopyrrolidin-1-yl ester (TPN) was initially developed by the Gao group for free radical-initiated peptide sequencing (FRIPS) of hydrophobic peptides. , The relatively low BDE (30 kcal/mol) of the C–O bond facilitated the loss of 2,2,6,6-tetramethylpiperidine- N -oxyl radical (TEMPO·, 156 Da) upon CID and then triggered RDD within the peptide backbone. Our group later demonstrated that methyl branching, cyclopropane, and hydroxyl modifications could be localized upon CID of TPN-derivatized phosphatidylethanolamine ions. , In this study, we further expanded the analytical scope of CID-triggered RDD via TPN derivatization for the analysis of sphingoid bases. This method was integrated onto an RPLC-MS/MS workflow to realize the identification and relative quantitation of sphingoid bases hydrolyzed from bovine heart and Nematoda C. elegans .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…3-(2,2,6,6-Tetramethylpiperidin-1-yloxymethyl)-picolinic acid 2,5-dioxopyrrolidin-1-yl ester (TPN) was initially developed by the Gao group for free radical-initiated peptide sequencing (FRIPS) of hydrophobic peptides. , The relatively low BDE (30 kcal/mol) of the C–O bond facilitated the loss of 2,2,6,6-tetramethylpiperidine- N -oxyl radical (TEMPO·, 156 Da) upon CID and then triggered RDD within the peptide backbone. Our group later demonstrated that methyl branching, cyclopropane, and hydroxyl modifications could be localized upon CID of TPN-derivatized phosphatidylethanolamine ions. , In this study, we further expanded the analytical scope of CID-triggered RDD via TPN derivatization for the analysis of sphingoid bases. This method was integrated onto an RPLC-MS/MS workflow to realize the identification and relative quantitation of sphingoid bases hydrolyzed from bovine heart and Nematoda C. elegans .…”
Section: Introductionmentioning
confidence: 86%
“…Barrientos et al proposed that both electronic and steric effects played roles in OzID of the 4E CC in glycosphingolipids . Regarding the PB reaction, steric hindrance posed by the headgroup might be the main reason because the oxidized PE containing an OH group at the α-position of a CC away from the headgroup showed comparable PB reaction yield to an unoxidized PE . More recently, by combining MS with cryogenic gas-phase infrared spectroscopy (cryoIR), the Pagel group achieved detailed structural assignment of standard glycosphingolipids including the identity of the glycan, α- or β-glycosidic linkage in the glycan, and the lipid moiety including sphingosine and phytosphingosine …”
Section: Introductionmentioning
confidence: 99%
“…While mass spectrometry based protocols provide exceptional sensitivity, specificity, and the ability to detect and quantify a wide range of lipid species involved in ferroptosis [ 281 ], they require specialized equipment, expertise, and sample preparation. The latest breakthroughs employing high-resolution mass spectrometry in conjunction with ion mobility and cutting-edge tandem mass spectrometry techniques have additionally enabled the direct identification of intact glycerophospholipids that bear oxidative labeling [ 282 , 283 ]. These advancements provide specific insights into the precise localization of these oxidative modifications [ 282 , 283 ].…”
Section: Methods For Monitoring Autophagy-dependent Ferroptosismentioning
confidence: 99%
“…The latest breakthroughs employing high-resolution mass spectrometry in conjunction with ion mobility and cutting-edge tandem mass spectrometry techniques have additionally enabled the direct identification of intact glycerophospholipids that bear oxidative labeling [ 282 , 283 ]. These advancements provide specific insights into the precise localization of these oxidative modifications [ 282 , 283 ]. Thiobarbituric acid reactive substances (TBARS) assay: The TBARS assay, which can be performed using commercial kits, is used to measure the levels of malondialdehyde (MDA), a product of lipid peroxidation [ 284 ].…”
Section: Methods For Monitoring Autophagy-dependent Ferroptosismentioning
confidence: 99%
“…The proposed derivatization reactions introduce functional groups in correspondence with the CC bonds based on the reactivity of alkenes that facilitate diagnostic cleavages, i.e., epoxidation with meta -chloroperoxybenzoic acid . The group of Xia first reported the application of the Paternò–Büchi (PB) photocycloaddition reaction with acetone for assigning the regiochemistry of CC bonds in untargeted lipidomics. , Several effective PB reactions have been proposed for improved conversion efficiency, compatibility with MS imaging, , enhanced reactivity under visible light, or compatibility with radical-directed dissociation . Our research group has recently proposed an aza-Paternò–Büchi (aPB) reaction complementary to the PB reaction that enables regiochemistry assignment in the negative ion mode (ESI−) rather than in positive polarity (ESI+). , One of the current issues related to PB and aPB is due to the multitude of isomers that derive from the photocycloaddition, that result in broad and split peaks with poor peak shapes when reversed-phase (RP) LC separation before HRMS is employed. , The peak splitting is mainly due to the inherent asymmetry of PB and aPB reagents; thus, different approaches would be needed to overcome this issue.…”
Section: Introductionmentioning
confidence: 99%